The activity of the landed gentry of the Kingdom of Poland during Warsaw’s agricultural and industrial exhibitions in the 19th century - Jarosław Kita (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku)
For two decades after the defeat of the January Uprising, the programme of organic work prevailed in the Kingdom of Poland, whose creators envisaged as one of the most important programme points the modernisation of society and the economy of the Polish lands, including agriculture. One of the important tools in the implementation of the programme was to be the organisation of agricultural and industrial exhibitions. After the January Uprising, four such exhibitions were held in Warsaw, and the first three were clearly dominated by sections related to agriculture and the food industry. They were attended by, among others, landowners of the Kingdom of Poland presenting their achievements. The aim of this article is to identify those most active representatives of the landed gentry community in the organisation of the exhibitions and their contribution to the modernisation of the economy, especially agriculture.